Intraluminal Behavior of Various Transporter Substrates in the Rat Gastrointestinal Tract - Yusuke Tanaka; Taiki Harada; Kazuhiro Ito; Takanori Kurakazu; Satoshi Kasaoka (Frontiers Media S.A., 2021)
Purpose: The aim of this study was to evaluate the intraluminal behavior of various transporter substrates in different regions of the gastrointestinal (GI) tract. Methods: Drug solutions containing non-absorbable FITC-dextran 4000 (FD-4), were orally administered to rats. Residual water was sampled from the GI regions to measure the luminal drug concentration. Results: Cephalexin (CEX), a substrate of the proton-coupled oligopeptide transporter, was absorbed rapidly, and no drug was detected in the lower small intestine. Saquinavir (SQV) was primarily absorbed in the upper region. However, unlike CEX, SQV was detected even in the lower segment probably due to the efflux of SQV via P-glycoprotein (P-gp). The concentration of methotrexate (MTX) showed a similar pattern to that of non-absorbable FD-4. The low absorption of MTX was probably due to efflux via several efflux transporters, and the limited expression of proton-coupled folate transporter, an absorptive transporter for MTX, in the upper region. Conclusion: This study revealed that the luminal concentration pattern of each drug differed considerably depending on the site because of the different absorption properties and luminal volumes. Although further investigation using a specific transporter inhibitor or transporter-knockout animals are necessary to clarify the actual contribution of each transporter to the drug absorption, this information will be valuable in evaluating transporter-mediated drug absorption in in vitro transport studies for ensuring optimal drug concentrations.